Fractional calculus for hydrology, soil science and geomechanics - Su, Ninghu (2020)
"This book presents the most relevant concepts and findings in fractional calculus (FC), fractional differential equations (FDEs) and fractional partial differentia equations (FPDEs) and their applications in soil physics, groundwater hydrology, soil mechanics, irrigation and drainage engineering, earth and environmental sciences and environmental engineering. Readers of this book will be postgraduates, senior undergraduates, academics, researchers and other professionals in these fields. A reader from the above fields will find the most relevant materials necessary for the initial study and immediate applications of the concepts and models with examples. It is the first book in soil science, hydrology and soil mechanics"--
Keywords: Hydrology -- Mathematical models; Soil science -- Mathematical models; Soil mechanics -- Mathematical models; Rock mechanics -- Mathematical models; Fractional calculus